Correlation of platelet count/splenic diameter ratio for the diagnosis of esophageal varices in patients of cirrhosis of liver - Mandar, Waghralkar; Vijay, Somannavar (International Journal of Research in Medical Sciences, 2021)
Background: In patients with cirrhosis, endoscopic screening for esophageal varices is currently recommended as a gold standard tool at the time of diagnosis of cirrhosis and to institute prophylactic measures in patients with large esophageal varices. Newer methods have been proposed as alternatives to conventional endoscopy for the non-invasive or minimally invasive diagnosis of esophageal varices. Methods: This one year observational study was done in the Department of Medicine at Dr. Prabhakar Kore Hospital MRC Belagavi. A total of 70 patients with cirrhosis of liver were included in the study. Relevant clinical examination, laboratory workup like complete blood count, liver function test, ultrasound abdomen and all patients underwent screening upper gastrointestinal endoscopy. Platelet count to spleen diameter ratio was calculated for all patients. Results: 54 (77.14%) had varices. Males predominated with 64 (91%). Majority patients ranged in between 31-50 years. Evidence of esophageal varices was more common with cirrhosis secondary to alcoholism as compared to hepatitis B virus (HBV) and hepatitis C virus (HCV). The child Pugh score, platelet count, spleen size, platelet count/spleen diameter ratio in patients with varices was significantly different from patients without varices. Platelet count spleen diameter ratio cutoff value of 909 was obtained with sensitivity of 77% and specificity of 79%. The positive predictive value was 88% and negative predictive value was 62%. Conclusions: The platelet count to spleen diameter ratio may be useful inexpensive tool for diagnosing esophageal varices in liver cirrhosis noninvasively when endoscopy facilities are not available.